2001
DOI: 10.1055/s-2001-13811
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Ultrasound Blood Flow Measurement of the Superior Mesenteric Artery Before and After Exercise

Abstract: This study examines the reproducibility of gastro-intestinal blood flow measurements in the superior mesenteric artery (SMA) both before and immediately after exercise with Doppler ultrasound measurements. Twelve well-trained males (mean +/- SD: age 25.9 +/- 3.8 yr; VO2max 4.8 +/- 0.91 x min(-1)) were measured twice (trial 1 and 2) with a 1 week interval before and immediately after 1 hr cycling at 70% VO2max. Duplex scanning was performed with the athletes in supine position immediately after transition from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Proposed etiologies for gastrointestinal dysfunction associated with running include gastrointestinal ischemia, the actions of GI hormones and neuropeptides released during exercise, endotoxemia, mechanical stimulation or trauma to the bowel, and exercise induced alterations of colonic motility 26,28,29 . Exercise, even at moderate intensity, can significantly reduce splanchnic blood flow, which may have consequences for mucosal integrity and intestinal contractility 30,31 . A recent study demonstrated mucosal destruction and altered intestinal contractility in a murine model of repetitive treadmill running 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Proposed etiologies for gastrointestinal dysfunction associated with running include gastrointestinal ischemia, the actions of GI hormones and neuropeptides released during exercise, endotoxemia, mechanical stimulation or trauma to the bowel, and exercise induced alterations of colonic motility 26,28,29 . Exercise, even at moderate intensity, can significantly reduce splanchnic blood flow, which may have consequences for mucosal integrity and intestinal contractility 30,31 . A recent study demonstrated mucosal destruction and altered intestinal contractility in a murine model of repetitive treadmill running 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Duration of exercise was indeed more prolonged in these studies, ranging from 12 to 30 min. Two studies also used direct measurement of the SMA to provide flow rates [38, 39]. The reproducibility of Eriksen’s findings has not been established in a study using similar duration, intensity and type of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Although data on the splanchnic vascular responses to maximal exercise have not been established, ischemia has been established frequently in these circumstances [3, 7]. In a study on splanchnic blood flow in trained volunteers, mean superior mesenteric artery blood flow fell by 38–49% after a 10-min exercise test at 70% of maximal workload [8]. It has been shown that the flow reduction in the celiac artery exceeds that of the superior mesenteric artery but still does not exceed about 50% [9].…”
Section: Discussionmentioning
confidence: 99%